ANALYSIS QUALITY CONTROL OF CREAMER PRODUCT PACKAGING USING DMAIC AND RCA METHODS - Umrin, Abdul Qodir; Wahyuni , Hana Catur (Journal for Technology and Science, 2025)
Objective: This study aims to analyze the types of defects in the packaging process of creamer products and propose improvements for the company based on data processing results. Method: The analysis utilizes a sigma index calculation supported by tools such as Pareto diagrams, fishbone diagrams for cause-and-effect evaluation, and failure tree diagrams to identify the root causes. The 5Whys method is also employed to analyze the underlying issues. Results: The findings indicate that while productivity remains stable, several factors contributing to a high percentage of packaging defects require evaluation and optimization. The analysis highlights specific areas for improvement in the packaging process. Novelty: This study introduces a comprehensive approach combining statistical tools and root cause analysis to optimize the packaging process in the creamer production industry, offering valuable insights for improving operational efficiency.